Lifelong Learning in the 21st Century: opportunities and challenges - Mansor Fadzil, (2016)
Keynote 2 presented by YB Prof Dr Mansor Fadzil, Prsedident/Vice-President Open University Malaysia (OUM) during ASEM Forum on Lifelong Learning, 3-5 October 2016, Copenhagen, Denmark